2020
DOI: 10.1101/2020.05.14.097121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PI3Kγ inhibition suppresses microglia/TAM accumulation in glioblastoma microenvironment to promote exceptional temozolomide response

Abstract: Precision medicine in oncology leverages clinical observations of exceptional response.Towards an understanding of the molecular features that define this response, we applied an integrated, multi-platform analysis of RNA profiles derived from clinically annotated glioblastoma samples. This analysis suggested that specimens from exceptional responders are characterized by decreased accumulation of microglia/macrophages in the glioblastoma microenvironment. Glioblastoma-associated microglia/macrophages secreted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…We find evidence in the literature supporting the effectiveness of these drug combinations. Li et al state that TMZ enhances the effect of TG100-115 on GBM cells and improves survival in mice [51]. Zhang et al show that the combination of LY2109761 and TMZ suppresses the tumor growth on T98G cell line.…”
Section: E Novel Predictionsmentioning
confidence: 99%
“…We find evidence in the literature supporting the effectiveness of these drug combinations. Li et al state that TMZ enhances the effect of TG100-115 on GBM cells and improves survival in mice [51]. Zhang et al show that the combination of LY2109761 and TMZ suppresses the tumor growth on T98G cell line.…”
Section: E Novel Predictionsmentioning
confidence: 99%
“…Recently, numerous studies have reported that TAM/Ms regulation may be a potential therapy strategy in cases with GBM. A new report demonstrated that PI3Kγ inhibition could suppress TAM/M accumulation in glioblastoma microenvironment, and enhance the anti-neoplastic effects of temozolomide in glioblastoma cells ( 43 ). In addition, the deletion of HuR (an RNA regulator) in TAM/Ms could attenuate glioma growth ( 44 ).…”
Section: Role Of Tam/ms In Glioblastomamentioning
confidence: 99%
“…GAMs not only drive the formation of immunosuppressive ME but also induce GBM stemness and enhance in vitro and in vivo tumorigenicity. Furthermore, human microglia can promote TMZ resistance by the augmented expression of inflammatory IL-11, which activates the STAT3 (signal transducer and activator of transcription 3)-MYC pathway in tumor cells ( 36 ). STAT3 activation is implicated in therapy resistance independent of MGMT methylation and in shaping the tumor ME by promoting M2 polarization in a signaling loop of immunosuppression and immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 activation is implicated in therapy resistance independent of MGMT methylation and in shaping the tumor ME by promoting M2 polarization in a signaling loop of immunosuppression and immune escape. PI3K (PhosphatidylInositol 3-Kinase)-γ inhibition reduces IL-11 accumulation in the tumor ME, which mimics the TMZ response of the so-called “exceptional responders” whose tumors show a reduced trafficking and infiltration of GAMs ( 36 ). The connection between the chemotherapy response and microglia is similarly evident from the capacity of TMZ-resistant GBM cells to promote M2 polarization by increased levels of lncRNA (long noncoding RNA) SNHG15 (small nucleolar RNA host gene 15).…”
Section: Introductionmentioning
confidence: 99%